Preparation method and application of sponge-loaded ionic covalent organic framework composite material

Through the sponge-loaded ionic covalent organic frame composite, the problems of traditional adsorbent recovery and environmental pollution are solved, and diclofenac sodium in wastewater are effectively removed, and good recycling and environmental protection characteristics are demonstrated.

CN119158549APending Publication Date: 2024-12-20XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410587840.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

When removing diclofenac sodium in wastewater, traditional ionic covalent organic frame adsorbents are difficult to recover and may cause secondary pollution in the environment, and their powdery form is difficult to effectively collect from the solution, affecting recycling.

Method used

Using sponge-loaded ionic covalent organic frame composite materials, synthesized by Schiff base reaction, using aldehyde-based monomers, amino monomers and melamine sponges to form composite materials with efficient adsorption and easy recovery, used to remove wastewater Diclofenac sodium.

Benefits of technology

It achieves efficient adsorption and removes diclofenac sodium, and does not require centrifugal operation through the design of the overall material, maintains the complete morphology of the adsorbent, avoids secondary pollution in the environment, and demonstrates good recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a sponge-loaded ionic covalent organic framework composite material, and the preparation method comprises the following steps: uniformly mixing melamine sponge, an amine organic matter (DGCl) and an aldehyde organic matter (TFPT), carrying out vacuum sealing on the mixture in a Slenker tube, and carrying out heating reaction to form an ionic covalent organic framework on the sponge, so as to obtain the sponge-loaded ionic covalent organic framework composite material. After the reaction, cooling to room temperature, and washing and drying a product to obtain the composite material. The sponge-loaded ionic covalent organic framework composite material disclosed by the invention realizes the function of efficiently adsorbing diclofenac sodium, still keeps the adsorption capacity of 85% or above after being recycled for five times, and has an excellent application prospect in the field of environmental pollution technical treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental pollution, and particularly relates to the synthesis of a sponge-loaded ionic covalent organic framework composite material and its application in adsorbing and removing diclofenac sodium in wastewater. Background Art

[0002] At present, tens of thousands of drugs such as antibiotics and anti-inflammatory drugs have been widely used in human treatment and animal husbandry. Diclofenac sodium is a widely used non-steroidal anti-inflammatory drug, usually used in the form of monosodium salt. It is worth noting that once diclofenac sodium and its derivatives are discharged into the environment, they will produce a series of negative effects such as drug resistance and threats to human health. However, due to its complex structure and difficult to degrade properties, diclofenac is usually difficult to remove in traditional wastewater treatment processes. Therefore, there is an urgent need to develop an efficient and reliable technology to remove diclofenac sodium from wastewater.

[0003] To date, researchers have used a variety of techniques to remove diclofenac sodium from wastewater, including membrane separation, adsorption, photodegradation, biodegradation, and oxidative degradation. Among them, adsorption is an attractive technique because it is simple, low-cost, and does not form toxic byproducts. Covalent organic frameworks (COFs) are crystalline porous materials covalently linked by light elements such as C, H, O, N, and B. Thanks to their tunable pore size, good thermochemical stability, and easy functionalization, COFs have been proven to be effective adsorbents for pollutant removal. Ionic covalent organic frameworks (iCOFs) are composed of an ionic skeleton and corresponding counterions and are a subclass of COFs. The advantage of iCOF in the adsorption of diclofenac sodium in solution is that it does not require post-modification and can directly utilize the ionic sites on the skeleton to provide uniform adsorption sites, thereby enhancing the electrostatic interaction with diclofenac sodium.

[0004] However, most traditional iCOF adsorbents are powders. After adsorption, it is difficult to collect powdered iCOF from the solution, which is not conducive to the cyclic adsorption process. At the same time, the unrecovered adsorbent may also cause secondary pollution to the environment. The development of a composite material formed by combining a support substrate with iCOF can solve the above problems. Melamine sponge (MS) is selected for its natural amino groups, low density, high porosity, high nitrogen content, three-dimensional (3D) pore structure, excellent mechanical properties and environmental friendliness. At present, some studies have reported the preparation of COF-modified sponges. For example, Wei invented a COF-coated melamine sponge for solid phase extraction of active ingredients of traditional Chinese medicine in serum samples in syringes [Anal Bioanal Chem414,8071–8079(2022).], and a sponge-supported porphyrin covalent organic framework monolithic material disclosed in Chinese patent application number CN202210025431.8 is used for adsorption and specific recognition of metal cadmium ions. However, there is no relevant literature or patent reporting on the adsorption and removal of diclofenac sodium in environmental wastewater by melamine sponge modified with ionic covalent organic framework.

[0005] The present invention combines the ionic covalent organic framework and the sponge for the first time, and the obtained composite material is applied to the field of non-steroidal anti-inflammatory drugs (diclofenac sodium) for the first time. Cl ) and melamine sponge (MS) are synthesized in one pot by Schiff base reaction to form a sponge-loaded ionic covalent organic framework. The composite material prepared by this invention has good practical application prospects in the adsorption and removal of diclofenac sodium in wastewater. Summary of the invention

[0006] The present invention provides a preparation method and application of a sponge-loaded ionic covalent organic framework composite material. The composite material not only retains the efficient adsorption capacity of iCOF itself for diclofenac sodium, but also realizes efficient recycling of the adsorbent.

[0007] In order to achieve the purpose of the present invention, the technical solution adopted by the present invention is:

[0008] The invention provides a preparation method of a sponge-supported ionic covalent organic framework composite material, comprising the following steps: using 4,4',4"-(1,3,5-triazine ring-2,4,6-triyl) tribenzaldehyde and 1,3-diaminoguanidine hydrochloride as starting materials, using glacial acetic acid as a catalyst in a reaction solvent, ultrasonically treating the mixture, adding washed and dried amino sponge, then vacuum-sealing a reaction container for heating reaction, and after the reaction is cooled to room temperature, washing and drying the product to obtain a composite material.

[0009] In some embodiments, the molar ratio of the 4,4',4"-(1,3,5-triazinecyclo-2,4,6-triyl)tribenzaldehyde to 1,3-diaminoguanidine hydrochloride is 2:3.

[0010] In some embodiments, the amino sponge is a melamine sponge.

[0011] In some embodiments, the solvent is N-methyl-2-pyrrolidone.

[0012] In some embodiments, the concentration of glacial acetic acid is 3M.

[0013] In some embodiments, the volume ratio of N-methyl-2-pyrrolidone and glacial acetic acid is (0.8-1.2):0.2.

[0014] In some embodiments, the reaction temperature is 120° C. and the reaction time is 3 days.

[0015] In some embodiments, the washing solvents are water, N,N-dimethylacetamide, tetrahydrofuran, acetone, and methanol, in that order.

[0016] In some embodiments, the vacuum drying temperature is 60°C.

[0017] The present invention also provides the use of the sponge-loaded ionic covalent organic framework composite material prepared by the above method for adsorbing and removing diclofenac sodium.

[0018] The advantages and beneficial effects of the present invention are:

[0019] (1) The sponge-loaded ionic covalent organic framework composite material of the present invention has a highly efficient adsorption and removal capability for diclofenac sodium.

[0020] (2) The sponge-loaded ionic covalent organic framework composite material of the present invention does not require centrifugation during use as a whole material, which is conducive to recovery and maintains the intact morphology of the adsorbent.

[0021] (3) The sponge-supported ionic covalent organic framework composite material of the present invention does not cause secondary environmental pollution when adsorbing and removing diclofenac sodium. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 These are scanning electron microscope images; (a) melamine sponge, (b) ionic covalent organic framework; (c) composite material.

[0023] Figure 2 are infrared images; (a) ionic covalent organic framework and its ligands, (b) melamine sponge and its composite materials.

[0024] Figure 3 is the X-ray powder diffraction pattern;

[0025] Figure 4 Schematic diagram of nitrogen adsorption; (a) adsorption-desorption curve of the composite material, (b) pore size distribution of the composite material.

[0026] Figure 5 Effect of solution pH on the adsorption of diclofenac sodium;

[0027] Figure 6 is the effect of solution salt ion concentration on the adsorption of diclofenac sodium;

[0028] Figure 7 is the adsorption equilibrium rate curve of the composite material to diclofenac sodium;

[0029] Figure 8 It is the adsorption temperature curve of the composite material to diclofenac sodium;

[0030] Fig. 9 This is a study chart on the adsorption-desorption cyclic usability of the composite material for diclofenac sodium. Specific implementation plan

[0031] The specific embodiments of the present invention are further described in detail in conjunction with the drawings in the examples. The following examples are used to illustrate the present invention, but do not limit the application scope and extension of the present invention.

[0032] Example 1: Preparation of sponge-supported ionic covalent organic framework composite materials

[0033] (1) Cleaning of melamine sponge

[0034] The melamine sponge was cut into small pieces of 0.5 cm × 0.5 cm × 0.5 cm, washed repeatedly with ethanol and water for several times, and then placed in a 60°C vacuum drying oven for 3 h to obtain a clean sponge.

[0035] (2) Synthesis of composite materials

[0036] 4,4',4"-(1,3,5-triazine-2,4,6-triyl) tribenzaldehyde (19.7 mg, 0.05 mmol) and 1,3-diaminoguanidine hydrochloride (9.5 mg, 0.075 mmol) were added to a 25 mL Slenker tube, and then 0.8 mL of N-methyl-2-pyrrolidone was added. The mixture was thoroughly mixed by ultrasonication for 30 seconds. After the cleaned amino sponge was added and stirred for 5 minutes, 0.2 mL of glacial acetic acid (3M) was added. The reaction container was evacuated and the mixture was reacted at 120°C in a closed environment for 3 days. After the reaction, the product was washed with water, N,N-dimethylacetamide, tetrahydrofuran, acetone, and methanol in turn, and then dried in a vacuum drying oven at 60°C for 6 to 8 hours to obtain a composite material.

[0037] Figure 1 The SEM images of melamine sponge, ionic covalent organic framework and composite material are shown in Figure 2. From the SEM images, the surface of the sponge alone is smooth and presents a three-dimensional network. The ionic covalent organic framework iCOF is an aggregate of short nanofibers with a coral-like structure. After loading iCOF, the sponge becomes rough and the fibrous structure of iCOF can be observed on the surface.

[0038] Figure 2 It is the infrared spectrum of the material. Figure 2 (a) The C=O (1708 cm -1 ) and the NH (3433 cm -1 ,3201cm -1 ) The characteristic stretching band disappears, and iCOF is at 1634cm -1 The imine (C=N) stretching vibration band appears. The sponge composite material prepared by the method of the present invention has a peak at 1635 cm -1 The characteristic peak of C=N bond stretching vibration of iCOF is shown by Figure 2 (b) shows the successful preparation of the surface composite material.

[0039] Figure 3 is the X-ray powder diffraction pattern of the material. iCOF has broad peaks at 2θ=3.5° and 5.9°, indicating low crystallinity, which is affected by the interaction between guanidine and Cl - The preparation of the composite material results in a decrease in crystallinity due to the charge repulsion between the two.

[0040] Figure 4 is a schematic diagram of nitrogen adsorption of materials. Figure 4 (a) It can be seen that the nitrogen adsorption isotherm of the composite material prepared by the present invention belongs to type IV, indicating that the material has microporous characteristics and a specific surface area of ​​81.75 m 2 / g, the poor control of the orientation of the guanidine units in the layer may be the reason for the relatively low specific surface area. Figure 4 (b) shows that the pore size of the composite material is

[0041] Embodiment 2:

[0042] (1) Weigh 3.0 mg of the sponge composite material adsorbent prepared in Example 1, add 12 mL of diclofenac sodium (100 mg / L) solution of different pH values, and shake at room temperature for 1 h. After sufficient adsorption, remove the adsorbent with tweezers, collect the supernatant, and use a UV-visible spectrophotometer to quantitatively analyze the content of the target substance before and after adsorption. The results are as follows: Figure 5 shown.

[0043] (2) From Figure 5It can be seen that when the pH is about 4.5, the adsorption capacity of the composite material for the target is the largest, and the adsorption amount gradually decreases with the increase of pH. This is because the N group on the iCOF in the composite material is easily protonated under acidic conditions and easily combines with anionic drugs. As the pH increases to the alkaline solution, the surface of the composite material has less positive charge, and it is difficult to adsorb the target with negative charge on the surface. Here, the pH range is selected from 4.5 because diclofenac sodium cannot be completely dissolved at pH 2 or 3.

[0044] Embodiment 3:

[0045] (1) Weigh 3.0 mg of the sponge composite material adsorbent prepared in Example 1, add 12 mL of diclofenac sodium (100 mg / L) solution containing different concentrations of different types of salt ions, and shake at room temperature for 1 h. After sufficient adsorption, the adsorbent is removed with tweezers, and the supernatant is collected. The content of the target substance before and after adsorption is quantitatively analyzed by UV-visible spectrophotometer. The results are as follows: Figure 6 shown.

[0046] (2) From Figure 6 It can be seen that due to the non-tetrahedral structure, Cl - and NO3 - The tetrahedral structure of SO4 has little effect on the adsorption of the target. 2- The adsorption capacity is reduced at higher concentrations, which is due to the fact that the binding affinity of the guanidine receptor for anions depends on the hydrogen bond donor ability and Coulombic stability. - ,The aqueous solution is alkaline, and the electrostatic interaction between the adsorbent and the target is weakened, thus reducing the adsorption amount.

[0047] Embodiment 4:

[0048] (1) Weigh 3.0 mg of the sponge composite material adsorbent prepared in Example 1, add 12 mL of a 100 mg / L diclofenac sodium solution, and oscillate at room temperature for 0 to 60 min. After sufficient adsorption, remove the adsorbent with tweezers, collect the supernatant, and use a UV-visible spectrophotometer to quantitatively analyze the content of the target substance before and after adsorption. The results are as follows: Figure 7 shown.

[0049] (2) By studying the adsorption capacity of the composite material for diclofenac sodium at different adsorption times, the following results were obtained: Figure 7 In order to further study the adsorption mechanism, the relationship between adsorption time and adsorption kinetics was studied based on the pseudo first-order (Largegren, 1898) and pseudo second-order (Blanachard et al., 1984) models, as shown in equations (1) and (2):

[0050] q t =q e[1-exp(-k1·t)] (1)

[0051]

[0052] Among them, q e (mg / g) and q t (mg / g) represent the adsorption amount at equilibrium and at time t (min), respectively, k1 and k2 (g·mg -1 ·min -1 ) are the pseudo-first-order kinetic and pseudo-second-order kinetic rate constants, respectively, and t (min) is the adsorption time.

[0053] The composite material was linearly fitted for the kinetics of diclofenac sodium, and the correlation coefficient (R 2 ) is smaller than the pseudo-second-order kinetics correlation coefficient. The adsorption is more consistent with pseudo-second-order kinetics and belongs to chemical adsorption.

[0054] Embodiment 5:

[0055] (1) Weigh 3.0 mg of the sponge composite material adsorbent prepared in Example 1, add 12 mL of a 20-120 mg / L diclofenac sodium solution, and shake at room temperature for 1 h. After sufficient adsorption, remove the adsorbent with tweezers, collect the supernatant, and use a UV-visible spectrophotometer to quantitatively analyze the content of the target substance before and after adsorption. The results are as follows: Figure 8 shown.

[0056] (2) By studying the adsorption capacity of the composite material for diclofenac sodium at different target concentrations, the following results were obtained: Figure 8 The curve graph is shown. Langmuir and Freundlich models are used to simulate the experimental data. Their equations are expressed as formula (3) and formula (4) respectively:

[0057]

[0058]

[0059] Among them, q e (mg / g) and Q m (mg / g) represent the equilibrium adsorption capacity and the maximum adsorption capacity, respectively, K L (L / mg) is the Langmuir equilibrium constant, C e (mg / L) is the equilibrium concentration, K F (g / mg) is the Freundlich equilibrium constant, n F is the Freundlich index.

[0060] (3) The final fitting results are shown in Table 1. The linear form of the Langmuir model of the composite material adsorption of diclofenac sodium (R 2 ) is higher than that of the Freundlich model, indicating that the Langmuir model can well describe its adsorption behavior.

[0061] Table 1 Adsorption thermodynamic equilibrium constants of diclofenac sodium

[0062]

[0063] Embodiment 6:

[0064] The target diclofenac sodium can be easily eluted by treating the adsorbent material with 0.1% NaOH in methanol. The regenerated composite material maintained a removal capacity of more than 85% for the target after 5 consecutive cycles. Fig. 9 As shown, this proves that the composite material prepared by the present invention has good recyclability and is conducive to practical application.

Claims

1. Preparation of a sponge-supported ionic covalent organic framework composite material, characterized in that: 4,4',4"-(1,3,5-triazine-2,4,6-triyl) tribenzaldehyde and 1,3-diaminoguanidine hydrochloride are used as starting materials, glacial acetic acid is used as a catalyst in a reaction solvent, the mixture is ultrasonically treated, and then a washed and dried amino sponge is added. The reaction container is vacuum-sealed for heating reaction. After the reaction is cooled to room temperature, the product is washed and dried to obtain a composite material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tribenzaldehyde to 1,3-diaminoguanidine hydrochloride in step 1 is 2:

3.

3. The preparation method according to claim 1, characterized in that: The amino sponge described in step 1 is melamine sponge.

4. The preparation method according to claim 1, characterized in that: In step 1, the solvent is N-methyl-2-pyrrolidone, the concentration of glacial acetic acid is 3M, and the volume ratio of N-methyl-2-pyrrolidone to glacial acetic acid is (0.8-1.2):0.

2.

5. The preparation method according to claim 1, characterized in that: The reaction temperature in step 1 is 120° C. and the reaction time is 3 days.

6. The preparation method according to claim 1, characterized in that: During the washing in step 1, water, N,N-dimethylacetamide, tetrahydrofuran, acetone and methanol are used in sequence for washing, and then vacuum drying is performed at 60°C.

7. A sponge-supported ionic covalent organic framework composite material, characterized in that: Prepared by the method according to any one of claims 1 to 6.

8. The application of the sponge-loaded ionic covalent organic framework composite material for adsorption of non-steroidal anti-inflammatory drugs according to claim 7, characterized in that: The non-steroidal anti-inflammatory drug is diclofenac sodium.

9. The use of the composite material according to claim 8 for adsorption of diclofenac sodium, characterized in that: The concentration range of the diclofenac sodium solution is 20-120 mg / L, the adsorption time is 0-60 min, and the dosage ratio of the adsorbent to the adsorbate is 1 g:4 L.

10. The use of the composite material according to claim 8 for adsorption of diclofenac sodium, characterized in that: The pH range of the solution is 4.5-10.

11. The use of the composite material according to claim 8 for adsorption of diclofenac sodium, characterized in that: The eluent after adsorption was 0.1% NaOH in methanol.